(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Treatment of patients with corneal leukomas complicated by detachment of the retina or other vitreoretinal pathology is a complex task due to little experience and a combination of numerous peculiarities of the pathological process in each separately taken clinical case. Purpose. To investigate efficacy of the combined surgical treatment of patients with corneal leukomas and vitreoretinal pathology by using temporary keratoprosthesis. Material and methods. The combined operative intervention is performed for retinal detachment: in 11 eyes (10 patients) with corneal leukomas after severe chemical burn, of them 6 eyes were after earlier performed keratoprosthesis; one patient had endothehal-epithelial dystrophy of the cornea (EED) developed after extracapsular extraction of the cataract. On vitrectomy there was used the temporary keratoprosthesis of the modification of Massachusetts Eye and Ear Infirmary, Boston. Results. Complete conformity of the retina on the operational table was achieved in 11 of 12 eyes that has allowed to restore sight in 3 eyes with keratoprosthesis, to keep light sensation in 6 eyes, to perform keratoprosthesis in the subsequent 3 of them and to receive little uniform sight. Light sensation has been lost in 2 eyes after surgery.Conclusions. Application of the temporary keratoprosthesis in the eyes with leukomas allows to perform standard vitrectomy and to eliminate available detachment of the retina and other vitreoretinal pathology.